2016
DOI: 10.1371/journal.pone.0147089
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Reveals OTA-Related Gene Transcriptional Changes in Aspergillus carbonarius

Abstract: Ochratoxin A (OTA) is a mycotoxin harmful for animals and humans. Aspergillus carbonarius is the main responsible for OTA contamination of grapes and derived products. Gene transcriptional profiling of 4 A. carbonarius strains was carried out by RNA-Seq analysis to study transcriptome changes associated with OTA production. By comparing OTA inducing (OTAI) vs. non-inducing (OTAN) cultural conditions, a total of 3,705 differentially expressed genes (DEGs) (fold change > |2| and FDR ≤ 0.05) were identified. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 62 publications
1
41
0
Order By: Relevance
“…ochraceus. The transcriptome analysis of A. carbonarius strains under OTA inducing conditions showed that AcOTApks, AcOTAnrps, AcOTAp450, and AcOTAhal were highly up-regulated in OTA inducing conditions and all were co-expressed in addition to the AcOTAbZIP (Gerin et al, 2016) supporting the fact that the cluster 38 is likely the OTA gen cluster in A. carbonarius.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…ochraceus. The transcriptome analysis of A. carbonarius strains under OTA inducing conditions showed that AcOTApks, AcOTAnrps, AcOTAp450, and AcOTAhal were highly up-regulated in OTA inducing conditions and all were co-expressed in addition to the AcOTAbZIP (Gerin et al, 2016) supporting the fact that the cluster 38 is likely the OTA gen cluster in A. carbonarius.…”
Section: Discussionmentioning
confidence: 88%
“…carbonarius strains under OTA induction conditions (Gerin et al, 2016). In the nonochratoxigenic strains an oxalacetate acetylhidrolase (ID 158065) was down-regulated.…”
Section: Differential Gene Expression and Functional Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…The halogenase gene was associated with OTA biosynthesis by use of differentialdisplay reverse transcriptase PCR (RT-PCR) with P. nordicum grown on minimal media either suitable or inadequate for OTA production (15). Transcriptome sequencing (RNA-Seq) and reverse transcriptase quantitative PCR (RT-qPCR) analysis were used to associate a PKS, an NRPS, and a chloroperoxidase with the OTA biosynthetic process (38).…”
Section: Discussionmentioning
confidence: 99%